Wind load effect on train station - Mohd Fahmi Abdul Rahim, Mohd Fahmi (2009)
This project investigates of the effect of the pressure distribution of a journal bearing by varying the viscosity of the lubricant. This paper mainly consists of two parts which is experimental and theoretical calculation.